A functional variable universe fuzzy PID controller for load following operation of PWR with the multiple model. (1st June 2020) - Zeng, Wenjie; Jiang, Qingfeng; Xie, Jinsen; Yu, Tao
Highlights: The multiple model of reactor core is developed. The FVUF-PID controller is used to design a global controller for core power control. The global controller with the multiple model strategy is designed to load following of a PWR. Abstract: To achieve core power control of Pressurized Water Reactor (PWR) over full power range under arbitrary initial power conditions, a global controller under the multiple model for reactor core load following is designed. Based on the nonlinear model of PWR core, the transfer function models at five power levels are chosen as local models of reactor core. The multiple model of PWR core in the global range of power level is the weighted sum of five local models with the triangle membership functions. Based on the multiple model of PWR core, a global controller, is contrived by five local controllers at different core power level with the Functional Variable Universe Fuzzy PID (FVUF-PID) controller. The simulation results show that the global controller has good convergence and performance robustness characteristics over a wide range of operational parameters.